Synthesis, crystal structure, thermal analysis and biological activities of sodium 5-carboxy-2, 3-dihydroxybenzenesulfonate. (12th April 2016) - Wei, J.; Liu, K.; Lin, F.; Zhou, Y.; Zou, J.; Lin, C.
ABSTRACT: Through the sulfonation of protocatechuic acid, sodium 5-carboxy-2, 3-dihydroxybenzenesulfonate (SPA ) was synthesized. The structure of the sulfonated derivative was confirmed by FT-IR, MS, 1 H NMR, 13 C NMR, single crystal X-ray diffraction, and thermogravimetric analysis. The antioxidative activities of the derivativeSPA were evaluated using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) scavenging method and reducing power determination, showing thatSPA had strong antioxidative effects. Meanwhile DPPH scavenging progress bySPA was analyzed from dynamics experiments. Isothermal titration calorimetry (ITC) and circular dichroism (CD) were applied to investigate the interaction between the derivativeSPA and human serum albumin (HSA).